1997
DOI: 10.1111/j.1471-0528.1997.tb11052.x
|View full text |Cite
|
Sign up to set email alerts
|

Human placental syncytiotrophoblast microvillous membranes impair maternal vascular endothelial function

Abstract: Objective To investigate the hypothesis that, should there be an increase in deported syncytiotrophoblast microvillous membrane fragments in pre-eclampsia, it may cause maternal vascular endothelial dysfunction.Design Syncytiotrophoblast microvillous membrane (STBM) vesicles, prepared from normal term placentae, were perfused through small subcutaneous arteries isolated from fat biopsies obtained at caesarean section. Endothelial function of these arteries was studied by determining acetylcholineinduced relaxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
1
10

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 20 publications
4
83
1
10
Order By: Relevance
“…Furthermore, vesicles prepared from STBM reduced the relaxation response of preconstricted subcutaneous fat arteries from normotensive pregnant women to acetylcholine, presumably due to decreased endothelial dependent relaxation. 164 Thus some of the endothelial dysfunction seen in PE might be secondary to the consequences of increased trophoblast invasion.…”
Section: Placentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, vesicles prepared from STBM reduced the relaxation response of preconstricted subcutaneous fat arteries from normotensive pregnant women to acetylcholine, presumably due to decreased endothelial dependent relaxation. 164 Thus some of the endothelial dysfunction seen in PE might be secondary to the consequences of increased trophoblast invasion.…”
Section: Placentationmentioning
confidence: 99%
“…162 The local generation of nitric oxide (NO) may also be involved; there is increased NO activity in the veins of the dorsum of the hand in pregnancy. 163 Blood flow itself is a major regulator of endothelial NO synthesis, and Cockell et al (1997) 164 have shown in small arteries from fat biopsies in healthy pregnant women that NO responses to flow are enhanced by comparison with those from non-pregnant subjects. Furthermore, the forearm vascular response to NO synthase inhibition is enhanced in normal pregnancy by comparison with non-pregnant women, also suggesting a rô le for NO in the vasodilatation of pregnancy.…”
Section: The Cardiovascular Systemmentioning
confidence: 99%
“…Bit Na Rae Kim, et al Serum nephrin expression in preeclampsia 위자 체계 등이 관여하는데, 이 과정에서 중요한 역할을 하는 것이 혈 관 형성인자들이다 [7][8][9]. 태반 형성과정에 이상이 생기면 태반에 허 혈이 생기고 그에 따라 전신적으로 세포독성물질들이 분비되어 모체 의 혈관 내피에 손상을 주게 된다 [12].…”
unclassified
“…태반 형성과정에 이상이 생기면 태반에 허 혈이 생기고 그에 따라 전신적으로 세포독성물질들이 분비되어 모체 의 혈관 내피에 손상을 주게 된다 [12]. 또한 최근 연구들에 따르면 전 자간증에서 혈관 형성인자들의 조절에 이상 소견이 보이는 것이 밝혀 졌다 [1,9,[13][14][15][16][17][18][19][20]. 그 대표적인 혈관 형성인자들이 placental growth factor (PlGF), soluble fms-like tyrosine kinase-1 (sFlt-1), vascular endothelial growth factor (VEGF) 등이다.…”
unclassified
See 1 more Smart Citation